Glycine and Riboflavin Detoxification of Ackee Apple Seeds (Blighia sapida): Effects on Blood, Git and Organ Development in Broilers - Annongu, A.A.; Joseph, J.K.; Apata, D.F.; Adeyina , A.O.; Kayode, R.M.O.; Badmos, A.H.A.; Awopetu, V. (International Journal of Poultry Science, 2013)
Ackee Apple Seeds (AAS) subjected to chemical detoxification with glycine and riboflavin at 5% coupled with traditional treatments of soaking and boiling to leach out some soluble AAS toxins, hypoglycin A and B, was evaluated for nutritional adequacy using day chicks (DOC). Six iso-caloric and nitrogenous diets were prepared with graded levels of 2.5, 5.0, 7.5, 10.0 and 12.5% AAS meal in rations 2, 3, 4, 5 and 6 respectively. The diets including a corn-soybeans control diet were fed ad libitum to 144-DOC in a 4-week feeding trial. Results showed that the test feedstuff improved blood composition (PCV, WBC). The non- significant difference recorded on lengths of GIT parts including ileum and duodenum relative to the reference diet suggest the similarity of the test diets with the conventional diet (p>0.05). Differences observed on absolute and relative organ weights (AOW and ROW) supported the result on performance which gave significant increase in body weight gain (p<0.05). Results on hematology, GIT, AOW and ROW following detoxified AAS meal ingestion suggest that the methods offer great potential for effective detoxification of Ackee apple seeds.